THE EFFECTS OF DIFFERENT LEVELS OF ENERGY AND ITS OIL SOURSE ON BROILER PERFORMANCE - K. Moussoh , S.; S. Mohammed , A. (The Iraqi Journal of Veterinary Medicine, 1989)
This experiment was carried out at poultry farms College of Agriculture University of Baghdad to study the effects of three different levels of metabolizable energy 3000, 3200, 3400 Kcal per kg. of diet on broiler performance Two different levels of energy obtained from oil witnin each level of metabolizable energy. The results shouied that within each level of metabolizaole energy, there were significant differences in body weignt between groups received medium and high energy from fat at 8 weeks of age, but was not so at 3 and 6 weeks of age. There were no significant differences in feed conversion rate at three weeks of age but were significant at six and eight weeks of age. In dressing percentage and mortality there were no significant differences between the six groups.